Pretilachlor Releasable Polyurea Microcapsules Suspension Optimization and Its Paddy Field Weeding Investigation - Chen, Hongjun; Liu, Xiu; Deng, Shuqi; Wang, Hongkun; Ou, Xiaoming; Huang, Linya; Li, Jingbo; Jin, Chenzhong (Frontiers in Chemistry, 2020)
In this study, pretilachlor was encapsulated into polyurea microcapsules prepared by water-initiated polymerization of polyaryl polymethylene isocyanate and eventually made into pretilachlor microcapsules suspension (PMS). Response surface methodology (RSM) combined with the Box–Behnken design (BBD) model was used to optimize formulation of PMS. The encapsulation efficiency (EE) of PMS was investigated with respect to three independent variables including wall material dosage (X1), emulsifier dosage (X2) and polymerization stirring speed (X3). The results showed that the regression equation model had a satisfactory accuracy in predicting the EE of PMS. To achieve an optimal condition for PMS preparation, the dose of wall material was set to 5%, the dose of emulsifier was set to 3.5% and the polymerization stirring speed was set to 200 rpm. The EE of PMS was up to 95.68% under the optimized condition, and the spherical shape with smooth surface morphology was observed. In addition, PMS was also proved to have delayed release capability and in vivo herbicidal activity against barnyard grass (Echinochloa crusgalli (L.) Beauv.) with LC50 value of 274 g/mL. Furthermore, PMS was proved to have efficient weed management compared to commercially available 30% pretilachlor emulsifier (PE), showing a promising application potential for weeding in paddy fields.